Effectiveness of a Green Analytical Chemistry-Based Problem-Based Learning Model in Improving Environmental Literacy among Pharmacy Students - UZ, LM Zulfahrin; Susilana, Rudi; Wahyu, Wawan (ISEJ : Indonesian Science Education Journal, 2026)
This study aims to analyse the effectiveness of the Green Analytical Chemistry (GAC)-based Problem-Based Learning (PBL) model in improving pharmacy students' environmental literacy. This study used a quasi-experimental design with a Nonequivalent Control Group Pretest–Posttest Design. The study sample consisted of 60 Pharmacy Study Program students divided into an experimental group and a control group. The experimental group received GAC-based PBL, while the control group received direct instruction. The treatment was carried out over five meetings on the following topics: basic analytical chemistry techniques, physical and chemical properties of drug molecules, acids and bases, instrumental analysis, and reduction–oxidation reactions. The research instrument was an environmental literacy test that measured environmental knowledge, attitudes, environmental problem-solving competencies, and environmental behaviour. Data were analysed using the N-Gain test, Independent Samples t-test, and Cohen's d. The results showed that the experimental group achieved a greater increase in environmental literacy than the control group, with N-Gain values of 0.7040 and 0.3963, respectively. The results of the Independent Samples t-test showed a significant difference between the two groups (p < 0.05). The findings of this study indicate that the PBL model based on Green Analytical Chemistry was effective in improving the environmental literacy of pharmacy students.